Nutritional status among people living with HIV receiving antiretroviral medication at Hospital Sungai Buloh, Malaysia - Hejazi, Nazisa (2009)
Lack of information on the nutritional status of PLHIV in Malaysia prompted this cross-sectional study of 340 HIV -positive adults receiving antiretroviral medication at Hospital Sungai Buloh in order to determine their nutritional status as well as identify those factors associated with it. Respondents were selected based on two-stage proportional stratified sampling among all patients receiving HIV treatment at the Infectious Disease Clinic of the Sungai Buloh Hospital. A pretested questionnaire was used to collect information on socioeconomics, and dietary intake using face to face interview. Medical history, health status and antiretroviral CARY) regimen were obtained from respondents' computerized medical records. Biochemical parameters including lipid profile,hematological and immunological parameters were measured using fasting blood samples. Physical measurements included weight, height waist and. hip circumference, body composition and blood pressure. Descriptive statistics, comparative statistical procedures and multiple logistic regression were performed using SPSS version 16.0 Most respondents were men (78.8%), Chinese (63.8%), aged between 20 to 50 years (82.l%), had less than ten years of formal education (61.8%) and were employed (63.5%). All subjects were in the first stage of AIDS. The majority (94.6%) had been taking ARV medications for more than six months. The prevalence of elevated total cholesterol level (65.8%), LDL-C level (78.4%), low HDL-C level (39.8%), elevated triglycerides level (62.2%), fasting plasma glucose (22.0%) metabolic syndrome (27.9%) according to National Cholesterol Education Program (NCEP), diabetes mellitus (10.9%) and hypertension (44.7%) were considerable. Megaloblastic anemia was very high (13.5%) as compared to the prevalence at the start of medication (2.5%). On the other hand, underweight was more prevalent at start of medication. While 36.5% of the respondents had unhealthy waisthip ratio, 85.l% had optimal body composition based on fat and fat free mass. The majority of respondents had insufficient dietary intakes although males had higher mean food intakes. Rice, green leafy vegetables and fresh sea fish were the most frequently consumed food items.Education attainment was higher among Indians while Chinese respondents had higher monthly household incomes and had been on treatment for a longer period. More than half of all ethnic groups had abnormal lipid levels. Wasting, abdominal obesity, metabolic syndrome and diabetes mellitus were more common among Indians. Malays as compared to other ethnic groups were more prone to megloblastic anemia and anemia in the form of reduced HCT. Ethnicity and gender had little influence on pattern of food consumption. Generally, males had higher socioeconomic status, prevalence of hypertension, metabolic syndrome and diabetes mellitus as compared to females. Apart from HDLC level, more females had elevated lipid level than males. All types of anemia were more commonly observed in females than males. The female subjects had more weight loss, wasting, underweight as well as overweight/obesity, abdominal obesity and higher percentage of body fat. Based on the results of multiple logistic regression, high waist circumference and waist hip ratio were the major risk factors for low HDL-C level and high triglycerides (components of metabolic syndrome) while age was a considerable risk factor in the occurrence of hypertension, anemia characterized by low hemoglobin level and also megaloblastic anemia. Body mass index (BMI) at start of ARV medication, energy intake, % energy from carbohydrate and % energy from fat were the risk factors for metabolic syndrome in this study.The present study demonstrated that PLHIV receiving ARV medication experience some nutritional abnormalities. Thus, the setting up of supportive and intervention programs should be introduced to prevent and reduce these health and nutritional complications that result both from of the infection as well as the ARV that they are on.